Body Dissatisfaction, Importance of Appearance, and Body Appreciation in Men and Women Over the Lifespan - Quittkat, Hannah L.; Hartmann, Andrea S.; Düsing, Rainer; Buhlmann, Ulrike; Vocks, Silja (Frontiers in Psychiatry, 2019)
Body image disturbance is associated with several mental disorders, including eating disorders and body dysmorphic disorder. Previous research on body image has focused mostly on women, largely neglecting body image in men. Studies assessing body image over the lifespan in a large population comprising males and females have rarely included participants aged 50 years and older. Furthermore, few studies have conducted comparisons of body image over the lifespan across genders. With regard to measurement, body image has often been assessed only in terms of body dissatisfaction, disregarding further aspects such as body appreciation or the importance of one’s appearance. The aim of this study was therefore to explore different aspects of body image in the general German-speaking population and to compare men and women of various age groups. Participants were recruited via social media and flyers and completed a short online survey comprising different questionnaires about body image. Body dissatisfaction, importance of one’s appearance, the number of hours per day participants would invest and the number of years they would sacrifice to achieve their ideal appearance, and body appreciation were assessed and analyzed with respect to gender and age differences. General and generalized linear models were used to examine the impact of age and gender. Body dissatisfaction was higher in women than in men and was unaffected by increasing age in women. Importance of appearance was higher in women than in men, but only for men did the importance of appearance decrease with age. Compared to men, women stated that they would invest more hours of their lives to achieve their ideal appearance. For both genders, the number of years that participants would sacrifice to achieve their ideal appearance decreased with age. With increasing age, body appreciation was higher in women than in men. Contrary to expectation, in women, increasing age predicted an increase in body appreciation. Men’s and women’s body image appears to have neutral to slightly positive connotations in the general population, irrespective of gender and age.